O direito à assistência integral no ambiente de saúde mental: uma análise do hospital municipal São Camilo de Lellis - Vale, Wanderson Victor Moura (Universidade Federal Rural do Semi-Árido, 2017)
The Psychiatric Reform has shown a break with asylum institutions. More than that, it proposed a new therapeutic model in the field of mental health, guaranteeing several fundamental rights to people in mental suffering, through a comprehensive treatment. The objective of this study is to develop an analysis about the role of the São Camilo de Lellis Municipal Hospital, located in the city of Mossoró / RN, in order to elucidate whether the institution complies with the guidelines established in Law 10.216 / 2001, and As in several federal regulatory ordinances. To this end, the guidelines of the Brazilian Reform were explained when addressing the new policy on mental health, stressing mainly the guarantee of a comprehensive treatment, through therapeutic services that guarantee the fundamental rights to people with mental disorders ordinarily foreseen, to the detriment of the old institutions with Characteristics. Therefore, the guidelines presented by the new care model with the activities carried out by the psychiatric hospital of Mossoró were compared using the data collected from the National Register of Health Establishments (CNES) and also from the answers related to the structured questionnaire submitted to the institution. At the end of this research, it was evidenced that even adopting various care measures in accordance with the new mental health policy, the Municipal Hospital São Camilo de Lellis continues to have asylum characteristics, mainly regarding medical superiority in treatment, Users in hospitals, as well as the fragility of the institution's integration with other services provided in the Psychosocial Care Network.
Monografia
Keywords: Direitos fundamentais; Instituições asilares; Reforma psiquiátrica; Saúde mental; Tratamento integral; Fundamental rights; Asylum institutions; Psychiatric reform; Mental health; Integral treatment; CIENCIAS SOCIAIS APLICADAS::DIREITO